2005
DOI: 10.1038/sj.bjc.6602525
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a new prognostic index score for disseminated nasopharyngeal carcinoma

Abstract: Patients with metastatic nasopharyngeal carcinoma have variable survival outcomes. We previously designed a scoring system to better prognosticate these patients. Here, we report results on validation of this new prognostic index score in a separate cohort of patients. Clinical features and laboratory parameters were examined in 172 patients with univariate and multivariate analyses and a numerical score was derived for each independent prognostic variable. Significant independent prognostic variables and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 34 publications
0
28
1
1
Order By: Relevance
“…However, the metastasis (Ⅳc) stage is still an 'all-embracing' classification, no matter any T, any N, and the metastasis site or number. But metastatic NPC makes a very heterogeneous group, of which the overall survival can range from weeks to years (Toh et al, 2005). As there was no great difference in the institutional treatment protocols, it cannot be satisfactorily explained by the therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the metastasis (Ⅳc) stage is still an 'all-embracing' classification, no matter any T, any N, and the metastasis site or number. But metastatic NPC makes a very heterogeneous group, of which the overall survival can range from weeks to years (Toh et al, 2005). As there was no great difference in the institutional treatment protocols, it cannot be satisfactorily explained by the therapies.…”
Section: Discussionmentioning
confidence: 99%
“…The median survival time ranges between 12.9-26.8 months (Toh et al, 2005;Cao et al, 2011;Lin et al, 2012). But a variable survival outcome is frequently observed in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several retrospective analyses have identified some unfavorable prognostic factors, including older age (4), anemia (5,6), poor performance status (5,6,14), short disease-free interval (4,5), prior chemotherapy (14), presence of liver metastasis (4-6, 14, 15), and multiple lesions (4,6,14). However, the application of these pretreatment markers into clinical practice with consequent adjustment of the treatment regimen has never been shown to be feasible.…”
Section: Discussionmentioning
confidence: 99%
“…However, advances in radiation oncology have improved the locoregional control, and treatment failure is now due mainly to distant metastasis. To date, the outcome of salvage treatment for relapse is still very poor, with the 5-year survival rates after local recurrence and distant metastasis being 9.4% to 30% and <5%, respectively (1)(2)(3)(4)(5)(6). Because most metastatic/recurrent patients will succumb rapidly to the disease, the development of a quick and precise marker to predict treatment response is urgently needed.…”
mentioning
confidence: 99%
“…Currently, evaluation of prognosis for metastatic NPC patients treated with palliative chemotherapy mainly relies on clinical characteristics, including performance status and disease-free interval. 8 There is still no reliable laboratory prognostic factor. Recently, several studies including our own data have shown that quantification of plasma Epstein-Barr virus (EBV) DNA by the real-time quantitative polymerase chain reaction (PCR) is a useful marker in the detection, monitoring, and prognostic prediction for nondisseminated NPC treated by radiotherapy.…”
mentioning
confidence: 99%